2021
DOI: 10.3389/fimmu.2021.733101
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 16 Weeks of Exercise Training on Neutrophil Functions in Breast Cancer Survivors

Abstract: Following therapy, breast cancer survivors (BCS) have an increased risk of infections because of age and cancer dysregulation of inflammation and neutrophil functions. Neutrophil functions may be improved by exercise training, although limited data exist on exercise and neutrophil functions in BCS.Sixteen BCS [mean age: 56 (SD 11) years old] completed 16 weeks of community-based exercise training and a 45-minute acute bout of cycling before (Base) and after (Final) the exercise training program. Exercise train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, several reports emphasized the positive effects of physical exercise and rehabilitation in increasing anti-inflammatory cytokines concentrations and promoting the release of anti-inflammatory regulatory T-cells ( Pierce et al, 2009 ; Mancuso, 2016 ). This hypothesis has been supported by preclinical and clinical studies highlighting the key role of physical exercise in the regulation of chemokine expression, promoting cytotoxic immune cell activity and downregulating suppressor immune cells ( Upadhyay et al, 2018 ; Liu et al, 2020 ; Bartlett et al, 2021 ). Accordingly, it is widely accepted that chronic inflammation biomarkers (i.e., interleukin 6 (IL-6), tumor necrosis factor-α (TNF-α), macrophage migration inhibitory factor (MIF), and C-reactive protein (CRP)) might have a role in the oncogenesis process, promoting their oncogenic effects in both genetic and epigenetic alterations ( Trinchieri, 2012 ; Zitvogel et al, 2017 ; Barabutis et al, 2018 ).…”
Section: Introductionmentioning
confidence: 85%
“…On the other hand, several reports emphasized the positive effects of physical exercise and rehabilitation in increasing anti-inflammatory cytokines concentrations and promoting the release of anti-inflammatory regulatory T-cells ( Pierce et al, 2009 ; Mancuso, 2016 ). This hypothesis has been supported by preclinical and clinical studies highlighting the key role of physical exercise in the regulation of chemokine expression, promoting cytotoxic immune cell activity and downregulating suppressor immune cells ( Upadhyay et al, 2018 ; Liu et al, 2020 ; Bartlett et al, 2021 ). Accordingly, it is widely accepted that chronic inflammation biomarkers (i.e., interleukin 6 (IL-6), tumor necrosis factor-α (TNF-α), macrophage migration inhibitory factor (MIF), and C-reactive protein (CRP)) might have a role in the oncogenesis process, promoting their oncogenic effects in both genetic and epigenetic alterations ( Trinchieri, 2012 ; Zitvogel et al, 2017 ; Barabutis et al, 2018 ).…”
Section: Introductionmentioning
confidence: 85%
“…For example, immune markers of NK cells differed: exercise had an inhibitory effect on the absolute number of NK cells in patients with breast cancer (106), an augmenting effect on NK cells percentages in patients with lung cancer (107), whereas no effect in another cohort of patients with breast cancer and other solid tumors was observed (17,22). Comparably, IL-6 expression differed after exercise interventions, showing either a decrease in some studies (24-26), but no effects (17,20,23,108), or an increase in other studies (16,18,109). Given the diverse effects that exercise has on the number of immune cells in patients with cancer, for instance in NK cells, it has been suggested that exercise may instead affect the cytotoxic activity of the immune cells, mirroring the effects exercise has on healthy individuals through inflammatory response pathways (110,111).…”
Section: Exercise and Conventional Cancer Therapiesmentioning
confidence: 98%
“…There is both pre-clinical and clinical evidence for a relation between exercise and the immune system and effectiveness of exercise during chemotherapy or radiotherapy (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). In patients, exercise has been associated with reduced side effects of cancer and its treatment (27, 28).…”
Section: Exercise and Conventional Cancer Therapiesmentioning
confidence: 99%
See 2 more Smart Citations